MEASUREMENT METHOD FOR DETERMINING THE RESIDUAL FLUX DEPOSITS IN A HEAT EXCHANGER FROM A CONTROLLED ATMOSPHERE BRAZING LINE - COCIAN, Grigore; POPA, Cătălin (Studia Universitatis Babeș-Bolyai Chemia, 2015)
The brazing technology of aluminum alloys having the highest efficiency, used at manufacturing heat exchangers, is the controlled atmosphere brazing with the NOCOLOK flux. The major inconvenience of the process is the residual flux retained on the internal surfaces of the heat exchanger, which in certain quantities may react with the cooling agents leading to gels that may compromise the functionality of the heat exchangers. The present paper presents a method of measuring the residual flux quantity based on the repeated experimentation and measurements taken on the horizontal, and vertical brazing manufacturing lines.